PENGARUH PEMBERIAN PUPUK ORGANIK CAIR DENGAN KOMPOSISI YANG BERBEDA TERHADAP PERTUMBUHAN TANAMAN STROBERI (Fragaria sp.) - Irawan, Hebi; Ardina Tanjungsari; Sapta Andaruisworo (UNIVERSITAS ISLAM LAMONGAN, 2024)
If the strawberry harvest is insufficient, market demand cannot be met. However, if the harvest is excessive, the strawberries are only used as animal feed or left to rot and become fertilizer. The aim of this study is to determine the effect of different compositions of liquid organic fertilizer on the growth of strawberry plants (Fragaria sp.). The research was conducted over 5 months from January to May 2024. The research method used a Completely Randomized Design (CRD). This study consisted of 4 (four) treatments and 3 (three) replications. The liquid organic fertilizer was made using organic materials, namely 0.5 kg of cow rumen, 0.2 l of molasses, 1 l of rice washing water, 0.5 l of rabbit urine, 0.5 kg of banana peels, 1 l of coconut water, and 0.5 kg of moringa leaves. The research treatments were as follows: P0 (liquid organic fertilizer at a concentration of 0 ml/1000 ml water), P1 (liquid organic fertilizer at a concentration of 100 ml/1000 ml), P2 (liquid organic fertilizer at a concentration of 200 ml/1000 ml), and P3 (liquid organic fertilizer at a concentration of 300 ml/1000 ml). Fertilization was done once a week for 1 month. The plant growth variables observed were plant height, number of leaves, number of stolon runners, and fruit weight. Based on the research results, the plant height variable for P2 resulted in the highest average plant height of 19.1 cm and was significantly different from the P0 and P3 treatments, but not significantly different from the P1 concentration. The leaf variable for the P2 liquid organic fertilizer treatment resulted in the highest average number of leaves at 15.7 leaves, followed by P1 and P3, with no significant difference. For the stolon runner variable, P2 produced the highest number of stolon runners at 1.0 stem, with no significant difference from the P0, P1, and P3 concentrations. The fruit weight variable for P2 produced the highest fruit production at 3.7 grams, with no significant difference from the P0, P1, and P3 concentrations.